Patients with osteoarthritis are least likely to receive lifestyle advice compared with patients with diabetes and hypertension: A national health survey study from Denmark. Issue 3 (September 2020) - Baumbach, Linda; Roos, Ewa M.; Lykkegaard, Jesper; Thomsen, Kristine Sloth; Kristensen, Peter Lund; Christensen, Anne Illemann; Thorlund, Jonas B.
Summary: Objectives: To investigate the association between having osteoarthritis (OA), hypertension, or diabetes, either alone or in combination, and receiving guideline-recommended exercise or weight-reduction advice. Design: Cross-sectional study. Methods: We applied logistic regression to analyse self-reported data from the 2017 Danish National Health survey (DNHS). We calculated the proportions and odds ratios of receiving exercise advice and weight-reduction advice (if BMI>30) from the general practitioner (GP) in seven patient groups: those with OA or hypertension or diabetes or any combination of these diseases. Results: From the 183, 372 DNHS responders, we included 71, 717 patients (≥45 years) who reported consulting a GP during the previous year. Among patients with only one disease, those with OA were least likely to receive exercise advice (13%, 1441/11, 024) and weight-reduction advice (27%, 504/1877), while those with diabetes were most likely to receive these advice (32%, 387/1200 and 55%, 160/289, respectively). For OA-only patients, the adjusted odds ratios of receiving exercise advice and weight-reduction advice were 1.4 (95% CI 1.3 to 1.5) and 1.6 (95% CI 1.4 to 1.8), respectively, compared with patients with none of the three diseases. For diabetes-only patients, the adjusted odds ratios were 4.2 (95% CI 3.7 to 4.7) and 5.4 (95% CI 4.2 to 7.0), respectively. Conclusion: Few patients with OA self-reported having received guideline-recommended exercise advice, or weight-reduction advice if obese, from their GP. Furthermore, patients with OA were less likely to report having received these advice compared with patients with other chronic diseases.